Assessment of work-life balance among Senior Female Administrators: A case study of the University of Cape Coast, Ghana - Asiedu Owusu, Rebecca (Ghana Journal of Higher Education Management, 2024)
Anecdotal evidence on burnout and untimely deaths in some public universities across Ghana has heightened the need for attainment of work-life balance. Juggling teaching, research, publishing and personal commitments can be a challenge in the academia. Using a concurrent triangulation mixed methods approach, this exploratory study assessed work-life balance of some 80 senior female administrators at the University of Cape Coast, Ghana. The results indicate that attainment of work-life balance depends on some variables such as age, marital status, parity and rank. The prospects of utilising technology to balance work and life seemed promising to promoting work-life balance for female senior administrators in the University. Although intuitive, four promoters of work life balance namely flexible work starting hours, flexible work closing hours, career break/sabbatical, and time-off for family engagements were explicitly identified by the respondents. The support of other family members such as partners was perceived to be a major fulcrum around which working women could attain work-life balance. It was recommended that Ghanaian women in public career spaces should be provided with conducive working environments like flexible working hours, extended paid maternity leave, paid paternity leave or provision of Early Childhood Centres closed to office environment. These also require national policy intervention on school vacations to allow schools keep lean staff during vacations to attend to children of career women.